2015
DOI: 10.1080/07399332.2015.1080261
|View full text |Cite
|
Sign up to set email alerts
|

Asia-Pacific women's experiences of stillbirth: A metasynthesis of qualitative literature

Abstract: Literature related to Asia-Pacific women's lived experiences of stillbirth was reviewed through metasynthesis of selected empirical studies. An overarching construct of "interconnectedness" between complex experiences influenced by cultural and systemic factors became apparent. Four experiential themes emerged: "acts of accusation," "rocky relationships," "entangled emotions," and "routines of reconciliation." These were influenced by two systemic factors: "contexts of culture" and "health care matters." Women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Like many LMICs, the Lao PDR healthcare system appears to be limited in its current capacity and capability to provide responsive care following stillbirth. Our key findings, especially in relation to limited data and review, lack of bereavement care for mothers and inadequate training and emotional support for healthcare providers, coincide with themes common to the small number of studies focused on care after stillbirth in LMICs [6][7][8].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Like many LMICs, the Lao PDR healthcare system appears to be limited in its current capacity and capability to provide responsive care following stillbirth. Our key findings, especially in relation to limited data and review, lack of bereavement care for mothers and inadequate training and emotional support for healthcare providers, coincide with themes common to the small number of studies focused on care after stillbirth in LMICs [6][7][8].…”
Section: Discussionsupporting
confidence: 61%
“…Available evidence suggests major shortcomings in the bereavement care provided due to a lack of health system resources and adequately trained healthcare providers [7]. Similarly, a review of seven qualitative studies of women's lived experiences of stillbirth in Asia-Pacific countries concluded that health systems and health professionals are 'often at a loss' as to the most appropriate care [8].…”
Section: Introductionmentioning
confidence: 99%
“…In Ireland, a stillborn baby is defined as an infant born with no sign of life weighing 500 g or more and/or having a gestational age of 24 weeks or more. Research shows that parents experience distress and sadness as they grieve for their baby and it has been found that how parents are counselled following stillbirth has lifelong impact . From the early literature, it was recognized by the medical community that women who were bereaved by stillbirth would be distressed, but it was felt that it would be in the best interest of the woman to have another baby in order to help put the loss behind her .…”
Section: Introductionmentioning
confidence: 99%
“…The struggle of whether to disclose the IUFD or not is echoed in the literature by the grieving mothers who experienced emotional pain, shame and guilt (Gopichandran, Subramaniam & Kalsingh 2018 ; Keeble & Thorsteinsson 2018 ). Furthermore, they experience social isolation and exclusion from friends, loved ones and family (Brierley-Jones et al 2015; Cacciatore 2010 ; Cheer 2016 ; Thompson 2013 ).…”
Section: Introductionmentioning
confidence: 99%